Identification and characterization of naturally occurring DSF‐family quorum sensing signal turnover system in the phytopathogen Xanthomonas. (27th August 2015) - Zhou, Lian; Wang, Xing‐Yu; Sun, Shuang; Yang, Li‐Chao; Jiang, Bo‐Le; He, Ya‐Wen
Summary: Molecules of the diffusible signal factor (DSF)‐family are a class of quorum sensing (QS) signals used by the phytopathogens X anthomonas . Studies during the last decade have outlined how X anthomonas cells enter the QS phase. However, information on the mechanism underlying its exit from the QS phase is limited. RpfB has recently been reported as a fatty acyl‐CoA ligase (FCL) that activates a wide range of fatty acids to their CoA esters in vitro . Here, we establish an improved quantification assay for DSF‐family signals using liquid chromatography‐mass spectrometry in X . campestris pv. campestris ( X cc ). We first demonstrated that RpfB represents a naturally occurring DSF‐family signal turnover system .  RpfB effectively turns over DSF‐family signals DSF and BDSF  in vivo . RpfB FCL enzymatic activity is required for DSF and BDSF turnover. Deletion of rpf B slightly increased X cc virulence in the Chinese radish and overexpression of rpf B significantly decreased virulence. We further showed that the expression of rpf B is growth phase‐dependent, and its expression is significantly enhanced when X cc cells enter the stationary phase. DSF regulates rpf B expression in a concentration‐dependent manner. rpf B expression is also negatively regulated by the DSF signalling components RpfC, RpfG and Clp. The global transcription factor Clp directly binds to the AATGC‐tgctgc‐GCATC motif in the promoter region of rpf B to repress its expression. Finally, RpfB‐dependent signal turnover system was detected in a wide range of bacterial species, suggesting that it is a conserved mechanism.